A colonial-decolonial critique of theological and religious research in South Africa (1975–2025) - Mujinga, Martin (2025)
As the Research Institute for Theology and Religion (RITR) celebrates 50 years of theological and religious research, reflecting on how the two have shaped South Africa’s history is essential. Religion and theology had been used as weapons of oppression and liberation. Before 1994, the two stood on two conflicting sides - the oppressor and the oppressed. The elite identified with the minority, while the majority of the poor craved an incarnate black God, who sides with the marginalised. The engagement of God in the Kairos Document, Black Theology and the decoloniality of theology in the post-apartheid era redefined God as one who is not static. Using a qualitative research methodology, this article aimed to explore the contours of the theological discourse employed by the RITR during the colonial and post-colonial eras. The article argued that the trajectory of theology from 1975 to 2025 demonstrates that God’s revelation takes different forms of the Godself. The need to redefine and redescribe a God who cannot be captured but remains incognito has been the major thrust of RITR; as such, celebrating the golden jubilee is a just cause. The article concluded by proposing future trajectories of theology in South Africa. Intradisciplinary and/or interdisciplinary implications: The trajectories of theology from the minority to the majority, from confrontational and defensive to decolonial theology in South Africa, demonstrate that religion and theology are not static, but rather the people’s socio-political and economic life continues to define and redefine the relationship between God and humanity.
Keywords: 1975–2025; 50 years; Black Consciousness; Black Theology; Decoloniality; Religion